Smart Collection of Waste Bread in Algeria Using the Internet of Things - Benabdallah, A. Y.; Boudour, R. (Engineering, Technology & Applied Science Research, 2022)
Algerians are among the largest consumers of bread throughout the year and produce large amounts of bread waste. As bread is made from imported wheat, these losses on currency are a heavy loss for the national economy. To minimize these losses, Algeria needs to encourage the recycling of stale bread to minimize the cost of importing soft wheat and valorize it for farmers. This paper presents a framework based on the Internet of Things (IoT) to monitor and collect waste bread from recycling bins. This system could assist Small and Medium Enterprises (SMEs) in Algeria in bread waste collection, by monitoring the level of filling of the outdoor waste bins. The proposed system’s architecture used a Mega 2560 microcontroller, HC-SR04 ultrasonic sensors, and SIM 808/900 modules.